Uterine infection with bovine herpesvirus type 4 in dairy cows - Klamminger, S. (2016)
Diseases of the reproductive tract are a frequent problem in dairy herds. Herpesviruses are uterine pathogens also involved in other clinical diseases; for example, bovine herpesvirus type 4 BoHV-4 induces abortion, enteritis, metritis, pneumonia and vaginitis, but it can also be detected in healthy cows. The role of BoHV-4 in the development of clinical endometritis (CE) or subclinical endometritis (SE) has not clearly been described. Therefore, the objective of this study was to describe the prevalence of uterine BoHV-4 infection and its relationship with clinical, bacteriological and cytological findings in dairy cows 20–30 days after calving. The experiment was performed as a completely randomized block design, with farm (n = 10) as blocking criterion and with cow (n = 397) as the experimental unit. Logistic regression models were used to assess the effect of BoHV-4 infection on CE, SE and reproductive performance. Proportion of cows infected with BoHV-4 was 5.8% (n = 23/397). BoHV-4 was isolated in 11.0% (n = 12/109), 4.8% (n = 4/84) and 3.6% (n = 7/194) of cows diagnosed as CE, SE or healthy, respectively. A logistic model revealed that BoHV-4 infection showed a tendency to increase the risk for CE (AOR = 2.17; p = .10) but significantly reduced both, the odds for artificial insemination within 80 days post-partum (dpp) (AOR = 0.37; p = .035) and for pregnancy within 200 dpp (AOR = 0.13; p = .004). Furthermore, BoHV-4 infection increased the chance for intrauterine infection with Trueperella pyogenes (AOR = 5.55; p < .001) and vice versa (AOR = 5.79, p < .001). In conclusion, BoHV-4 infection is associated with reduced chances for insemination and pregnancy by 200 dpp and showed a trend to be associated with increased risk for CE. Furthermore, BoHV-4 and Trueperella pyogenes infections are strongly related.